SYMBOLIC ANNIHILATION OF WOMEN IN THE CLASSIC JAPANESE CHILDREN’S FOLKTALE “KAGUYAHIME” - Fajria Noviana (Marwah: Jurnal Perempuan, Agama dan Jender, 2022)
Folktales intended for children have a significant role in shaping children's characters, including gender identities and roles. Nevertheless, literary works often portray women in stereotypical roles or even ignore them, which means that those works have carried out the symbolic annihilation of women. The purpose of this study is to describe the symbolic annihilations found in a classic Japanese children's folktale with a female main character entitled “Kaguyahime” which was published on the Pictio website in 2014. This research is a literature study that uses a qualitative paradigm with a feminist approach, using Tuchman’s concept of symbolic annihilation. As a result, it is known that the folktale “Kaguyahime” represents the views and thoughts of the Japanese nation, that adhere to a patriarchal ideology towards women. Japanese women experience symbolic annihilation in various manifestations, especially trivialization. They are constructed as weak beings who are not autonomous and are in the domestic sphere, which serves as some satisfactory for men's views.